The impact of remittances on human capital in Sub-Saharan countries - Chong, Siew Huay; Bani, Yasmin (International Foundation for Research and Development, 2023)
This study has examined the impact of remittances on human capital based on 23 Sub-Saharan countries (SSA) from 1981 to 2010. Our primary contribution lies in demonstrating that remittances have a positive impact on the enhancement of human capital in these SSA countries. The results indicate that a 1 percent increase in remittances leads to a 0.26 percent rise in the average years of schooling. To ensure the credibility of our findings, we employ a Generalized Method of Moments (GMM) approach to control for the endogeneity of remittances and human capital in our empirical analysis.